2011
DOI: 10.1007/s11356-011-0536-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability and ecotoxicitiy of tramadol, ranitidine, and their photoderivatives in the aquatic environment

Abstract: The study demonstrates that transformation products may have a higher environmental risk potential than the respective parent compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 27 publications
1
37
1
Order By: Relevance
“…Several studies have reported the presence and ecotoxicity of various pharmaceuticals in aquatic environment (Crane et al 2006, Fent et al 2006, Bergheim et al 2012. These compounds may affect sensitive nontarget organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the presence and ecotoxicity of various pharmaceuticals in aquatic environment (Crane et al 2006, Fent et al 2006, Bergheim et al 2012. These compounds may affect sensitive nontarget organisms.…”
Section: Introductionmentioning
confidence: 99%
“…[15] PECs were determined in accordance with the specifications of phase-I of the 'Guideline on the environmental risk assessment of medicinal products for human use' recommended by the EMA and as described elsewhere. [15,16] Briefly, the PEC (phase-I) is based on the maximum daily dose consumed per inhabitant (data from Germany used in this study), which is meant to be a representation of the daily and actual consumption rate in a worst-case scenario. Furthermore, a factor for market penetration is used as another first and simple approach to represent the proportion of inhabitants being treated daily with the specific active compound.…”
mentioning
confidence: 99%
“…Many of the PPCP biotransformation studies in the literature were carried out at higher concentrations than are commonly observed in the environment due to analytical sensi-tivity limitations, provision of the PPCP as the sole carbon and energy sources, and adherence to published biodegradation study protocols (e.g., Organisation for Economic Co-operation and Development [OECD] [11]). PPCP initial experimental concentrations greater than or equal to 1 mg liter Ϫ1 (even as high as 1.86 g liter Ϫ1 ) are not uncommon (12)(13)(14)(15)(16)(17). But with the wide range of concentrations found in the environment typically being less than 1 g liter Ϫ1 , it is unclear whether studies at higher concentrations can be extrapolated to predict the fate of PPCPs at environmentally relevant concentrations accurately.…”
mentioning
confidence: 99%